Community Empowerment Toward Environmental Sanitation And Example Jamban In Aek Sipitudae Village, Sianjur Mula Mula Mula, Samosir District - Tarigan, Lina; Tukiman (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2021)
Sanitation is one of the fundamental human rights aspects. Neglected sanitation development can have a broad impact, especially for health. Stopping open defecation is a major pillar that greatly affects public health, because this problem concerns environmental health issues that will have a broad impact on public health and a decrease in environmental quality. Environmental and sanitation quality degradation is a complex problem that occurs in Indonesia, including in Samosir Regency. There are still several villages that do not use latrines. Based on this, the community service team collaborated with the Samosir District Health Office to empower the community, among others, by providing counseling on environmental sanitation and inviting and motivating people to use the latrines provided and build latrines for those who do not. owning latrines through the construction of pilot latrines. It has been facilitated 16 goose neck latrines and 2 bags of cement for the 16 families who do not have latrines. The residents have been building and using pilot latrines. With this pilot latrine, it is hoped that it can increase the awareness of residents to change their habit of defecating so that later it can become a defecation-free village and improve the community's health status.